Antimicrobial Activity Of Neem (Azadirachta Indica A. Juss) Leaf Extracts Against Snakehead Fish (Channa Striata) Common Pathogens Aeromonas Hydrophila, Streptococcus Agalactiae, And Staphylococcus Xylosus - Musa, Senan Faik M. (2013)
The present study describes the potential of neem leaf (Azadirachta indica) extracts to control common bacterial fish pathogens under in-vitro and in-vivo conditions. The first experiment was conducted to assess the antimicrobial activity and minimum inhibitory concentrations of three crude extracts of neem (acetone, methyl alcohol and water), against three common fish pathogens Aeromonas hydrophila, Streptococcus agalactiae and Staphylococcus xylosus. Using well-diffusion methods invitro, the acetone extracts showed activity against all the tested bacteria with zones of inhibition at 13.25, 18.75 and 13.75 mg/ml respectively, while the methyl alcohol and water extracts showed activity only against A. hydrophila. Under in-vitro conditions, minimum inhibitory concentration determinations were conducted using a microdilution method. The acetone and methyl alcohol extracts showed the lowest MIC values, 0.078 and 0.156 mg/ml against S. agalactiae, respectively. A second experiment was conducted to evaluate the biological activities of the three crude extracts, using a brine shrimp (Artemia nauplii) toxicity bioassay. Among the three tested crude extracts, the water extracts showed the lowest toxicity, with LC50 values of 6.41 mg/ml within 24 hours. In the third experiment, the results of qualitative preliminary phytochemical screening of the non-toxic extract showed the presence of Flavonoids and Tannins.